Prototype Automation of Air Conditioning Treatment in the Grinding Area AK Based on IoT - Johan Eko Prasetyo; Jamaaluddin Jamaaluddin (Universitas Muhammadiyah Yogyakarta, 2021)
A good work environment will affect the level of productivity of workers in a company. The operation of the refrigeration machine in the cocoa powder grinding area is very important in production. The indicators for the operation of the cooling machine are dust density, ambient temperature and wind speed. With control on the indicator will increase efficiency. In this study, the indicator is controlled with a GP2Y1010AUF0F dust sensor, a DHT22 temperature sensor, a DS18B20 sensor, and a wind speed sensor as sensor inputs. Furthermore, the sensor will be processed by the Node M CU ESP826 module. System output will be displayed on LED and android. The results of this study indicate the accuracy of the dust sensor is 96.12%, the DHT22 temperature sensor is 99.80%, the DS18B20 temperature sensor is 99.57% and the speed sensor is 95.89%. In this prototype, we can monitor the temperature of the air velocity of dust particles in the engine and the temperature of the engine cooler together and closely monitored.